Reaction–diffusion chemistry implementation of associative memory neural network. Issue 1 (2nd January 2017) - Stovold, James; O'Keefe, Simon
Abstract : Unconventional computing paradigms are typically very difficult to program. By implementing efficient parallel control architectures such as artificial neural networks, we show that it is possible to program unconventional paradigms with relative ease. The work presented implements correlation matrix memories (a form of artificial neural network based on associative memory) in reaction–diffusion chemistry, and shows that implementations of such artificial neural networks can be trained and act in a similar way to conventional implementations. Graphical abstract: